Leadership in Action: Back to the Future: Putting Innovation Efforts on Solid Ground - Hipple, Jack; Hardy, David; Wilson, Steven; Michalski, James (Center for Creative Leadership, 2002)
The experiences of some former innovation champions contain lessons that can be used to plan and execute innovation efforts better the next time around.